2018
DOI: 10.1371/journal.pone.0204227
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in myotonic dystrophy type 1: Specific or secondary impairment?

Abstract: AimsThe cognitive profile of Myotonic Dystrophy type 1 (DM1) has been described in recent decades. Moreover, DM1 patients show lowered social engagement and difficulties in social-cognitive functions. The aim of the present study is to explore whether social cognition impairment is present in DM1 taking into account the overall cognitive condition.Method38 patients and a control group paired in age and gender participated in the study. All the participants had an IQ within the normal range. Subjects were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
3
21
2
2
Order By: Relevance
“…We have indeed confirmed the presence of difficulties in emotion processing (mainly for negative emotions) with our patients scoring below the normality cutoff when required to recognize not only sadness, embarrassment, and anger, but also happiness. Nevertheless, our findings are also partially different compared to those reported by Labayru et al (19), who found difficulties mainly in the recognition of anger and disgust. In our opinion, such differences are likely due to the different material used to assess emotions; indeed, Labayru et al (19) used a facial emotion recognition test, whereas in our patients, we evaluated the emotion attribution processing using brief verbal stories.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We have indeed confirmed the presence of difficulties in emotion processing (mainly for negative emotions) with our patients scoring below the normality cutoff when required to recognize not only sadness, embarrassment, and anger, but also happiness. Nevertheless, our findings are also partially different compared to those reported by Labayru et al (19), who found difficulties mainly in the recognition of anger and disgust. In our opinion, such differences are likely due to the different material used to assess emotions; indeed, Labayru et al (19) used a facial emotion recognition test, whereas in our patients, we evaluated the emotion attribution processing using brief verbal stories.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, our findings are also partially different compared to those reported by Labayru et al (19), who found difficulties mainly in the recognition of anger and disgust. In our opinion, such differences are likely due to the different material used to assess emotions; indeed, Labayru et al (19) used a facial emotion recognition test, whereas in our patients, we evaluated the emotion attribution processing using brief verbal stories. This test, which is part of the Social Cognition Battery, includes 58 brief stories that are read by the clinician.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations